A review and analysis of product recall for pharmaceutical drug product. (June 2022) - Miglani, Ashish; Saini, Chandan; Musyuni, Pankaj; Aggarwal, Geeta
The pharmaceutical industry's primary concern is to provide high-quality drug products to the general public, so drug recalls play an important role in maintaining the quality system by removing defective products from the market. Pharmaceutical product recalls are increasing at an alarming rate as a result of increased inspection rates and the introduction of modernization and the digital world into the industry, raising concerns for regulatory agencies and public health to focus on more stringent regulations to control future recalls of defective drug products. This article will provide an overview of recall procedures, their impact on the pharmaceutical industry, and the various steps taken to reduce pharmaceutical recalls.